Persepsi Mahasiswa Praktik Pengalaman Lapangan (PPL) terhadap Penggunaan Big Book pada Pembelajaran Bahasa Inggris - Salmiah, Maryati; Piliang, Wilda Srihastuty Handayani; Fitriany, Fitriany (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2022)
Reading literacy is one of the most important things to improve. One of the efforts that can be done is to train students of the Madrasah Ibtidaiyah teacher education study program to use big book as a medium that can improve the reading literacy skills of early grade students. Qualitative method is chosen to find out students' opinions on the use of big books for early-grade students. As many as 15 students of the Madrasah Ibtidaiyah teacher education study program were selected to use the big book as their learning medium when they were carrying out internships at five Madrasah Ibtidaiyah in the city of Medan. Each student shared their experience of using big book in the early grades of elementary school, this experience including the advantages and disadvantages of big book, their impressions, and suggestions on using Big book for early grade teachers.